2002
DOI: 10.1073/pnas.012025199
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of the human and mouse transcriptomes

Abstract: High-throughput gene expression profiling has become an important tool for investigating transcriptional activity in a variety of biological samples. To date, the vast majority of these experiments have focused on specific biological processes and perturbations. Here, we have generated and analyzed gene expression from a set of samples spanning a broad range of biological conditions. Specifically, we profiled gene expression from 91 human and mouse samples across a diverse array of tissues, organs, and cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
1,246
7
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,363 publications
(1,319 citation statements)
references
References 25 publications
59
1,246
7
7
Order By: Relevance
“…25 Four AAC isoforms have been identified in human with distinct expression patterns. 26,27 According to previous reports, [28][29][30] AAC2 and AAC3 are the dominant AACs in ECs. Co-IP confirmed that ISM interacts with AAC2/AAC3 (Figure 5a).…”
Section: Resultsmentioning
confidence: 92%
“…25 Four AAC isoforms have been identified in human with distinct expression patterns. 26,27 According to previous reports, [28][29][30] AAC2 and AAC3 are the dominant AACs in ECs. Co-IP confirmed that ISM interacts with AAC2/AAC3 (Figure 5a).…”
Section: Resultsmentioning
confidence: 92%
“…A recently published database provides microarray expression data for Affymetrix U95A chip, containing 12,600 probes, and hybridized to 101 different samples [9] from 47 different human tissues and cell lines. These samples are mainly from the normal human physiological state, and therefore this dataset provides a description of the normal mammalian transcriptome.…”
Section: Assignment Of Housekeeping Genesmentioning
confidence: 99%
“…The HK genes, which are transcribed in all somatic cells and under all circumstances, are by nature highly expressed, and therefore should be selected to have shorter introns. We used a recently published database of microarray experiments [9] to identify a set of HK genes. As a further validation step, we checked the Gene Ontology (GO) annotation of these genes.…”
mentioning
confidence: 99%
“…The expression information were retrieved from the GNF SymAtlas (http://symatlas.gnf.org). 21,22 The data were from the human HG-U133A and GNF1H chips, and the mouse GNF1M chip. Our study was focused on 29 orthologous (adult) tissues or cell types (referred to as ,tissues' for simplicity) shared by the mouse and human expression datasets, which are listed as follows: adipose tissue (at), adrenal gland (ag), amygdala (ad), bone marrow (bm), cerebellum (cb), CD4 + Tcells (T4), CD8 + Tcells (T8), dorsal root ganglion (dr), heart (ht), hypothalamus (hp), kidney (kn), liver (li), lung (lu), lymph node (ln), olfactory bulb (oc), ovary (ov), pancreas (pc), pituitary (pi), placenta (pl), prostate (pt), salivary gland (sg), skeletal muscle (sm), testis (ts), thymus (tm), thyroid (tr), tongue (to), trachea (tc), trigeminal (tg), and uterus (ur); the abbreviations in the parentheses were used in the context and figures.…”
Section: Datasetsmentioning
confidence: 99%